Census of the population 1930 - Occupational groups - Brantgärde, Lennart (University of Gothenburg, 2014)
This data collection contains information about total population and total number of professionally employed within the principal occupational groups agriculture and subsidiary industry, industry and craft, commerce and shipping, public service and independent professions, domestic work, and former professionally employed, and also within subgroups of these principal groups.

Denna datasamling innehåller information om totalbefolkningen och det totala antalet yrkesverksamma inom de övergripande yrkesklasserna jordbruk med binäringar, industri och hantverk, handel och samfärdsel, allmän förvaltningstjänst och fria yrken, husligt arbete samt f.d. yrkesutövare och även inom dessa klassers undergrupper.
Folkräkningen 1930 - Yrkesgrupper
Keywords: occupations; yrken; population; befolkning; census data; folkräkningsdata; rural population; landsbygdsbefolkning; urban population; stadsbefolkning; Censuses; Folkräkningar; Employment; Sysselsättning; HISTORY; HISTORIA; History; Historia